Audit quality and sentiment biases in going-concern opinions - Carlos André Marinho Vieira; Márcio André Veras Machado (Revista Contabilidade & Finanças)
ABSTRACT This research analyzed whether audit quality reduces sentiment biases existing in an auditor's opinion. Considering that measures based on data from opinion surveys have limitations regarding interpretation, and that aggregate measures using market data vary only in time series and not in cross-section, the results observed in this study bridge a major gap, by showing not only that sentiment influences an auditor's opinion, but also that a proxy for sentiment at the firm level is more appropriate than aggregate measures. Sentiment can influence an independent auditor’s opinion on the operational continuity of the client company and audit quality can reduce sentiment biases existing in an auditor’s opinion. In optimistic times, auditors subject to sentiment may be less likely to issue negative opinions on the operational continuity of audited companies undergoing financial difficulties. Considering audit quality as a characteristic of audit firms established a priori and based on the premises that higher audit quality is linked to greater auditor’s expertise, experience, and independence, it was expected that higher quality would be able to reduce sentiment biases existing in an auditor’s opinion. To test this hypothesis, 251 non-financial companies listed on the B3 were analyzed by using logistic regression within the period from 2010 to 2018. Firm-level sentiment showed a negative association with the probability of issuing going-concern opinions, indicating that auditors issue fewer negative opinions on the operational continuity of audited companies when firm sentiment is optimistic. Thus, evidence suggests that the research hypothesis is not rejected, considering that more independent auditors are able to mitigate the bias of this type of sentiment on their opinion regarding company operational continuity.